Um estudo exploratório envolvendo criptografia e fatoração numérica - Gomes, Fernanda Rodrigues (Universidade Federal de São Carlos, 2022)
This research aims to investigate the implications of applying a teaching sequence using cryptography and numerical factoring in the learning of 1st grade high school students. Cryptography has several applications in today’s society, from the security of accessing a social network to even the protection of banking data; In this sense, the research sought to present students from the history of cryptography to the functioning of RSA cryptography and the role of a hacker in this environment. We tried to make a didactic approach using videos, text, certificates from social networks and a final challenge. The students became "hackers of good", performing the factorization of compound numbers contained in the keys of the challenge and decoding the message of each urn using a pre-coded table, to arrive at the result.
An exploratory study involving cryptography and numerical factoring
Keywords: Cryptography RSA; Numerical Factorization; Hacker; Teaching; Criptografia RSA; Fatoração Numérica; Ensino; CIENCIAS EXATAS E DA TERRA::MATEMATICA